Early weaning stress in pigs impairs innate mucosal immune responses to enterotoxigenic E. coli challenge and exacerbates intestinal injury and clinical disease. - Brittney L McLamb; Amelia J Gibson; Elizabeth L Overman; Chad Stahl; Adam J Moeser (PLoS ONE, 2013)
The clinical onset and severity of intestinal disorders in humans and animals can be profoundly impacted by early life stress. Here we investigated the impact of early weaning stress in pigs on intestinal physiology, clinical disease, and immune response to subsequent challenge with enterotoxigenic F18 E. coli (ETEC).Pigs weaned from their dam at 16 d, 18 d, and 20 d of age were given a direct oral challenge of F18 ETEC at 26 d of age. Pigs were monitored from days 0 to 4 post-infection for clinical signs of disease. On Day 4 post-ETEC challenge, ileal barrier function, histopathologic and inflammatory cytokine analysis were performed on ileal mucosa.Early weaned pigs (16 d and 18 d weaning age) exhibited a more rapid onset and severity of diarrhea and reductions in weight gain in response to ETEC challenge compared with late weaned pigs (20 d weaning age). ETEC challenge induced intestinal barrier injury in early weaned pigs, indicated by reductions in ileal transepithelial electrical resistance (TER) and elevated FD4 flux rates, in early weaned pig ileum but not in late weaned pigs. ETEC-induced marked elevations in IL-6 and IL-8, neutrophil recruitment, and mast cell activation in late-weaned pigs; these responses were attenuated in early weaned pigs. TNF levels elevated in ETEC challenged ileal mucosa from early weaned pigs but not in other weaning age groups.These data demonstrate the early weaning stress can profoundly alter subsequent immune and physiology responses and clinical outcomes to subsequent infectious pathogen challenge. Given the link between early life stress and gastrointestinal diseases of animals and humans, a more fundamental understanding of the mechanisms by which early life stress impacts subsequent pathophysiologic intestinal responses has implications for the prevention and management of important GI disorders in humans and animals.